L-Citrulline Supports Vascular and Muscular Benefits of Exercise Training in Older Adults. Issue 3 (July 2020) - Figueroa, Arturo; Jaime, Salvador J.; Morita, Masahiko; Gonzales, Joaquin U.; Moinard, Christophe
Abstract : Age-associated reduction in endothelial nitric oxide (NO) synthesis contributes to the development of cardiovascular diseases and sarcopenia. L-Citrulline is a precursor of NO with the ability to improve vascular function and muscle protein synthesis. We hypothesize that vascular and muscular benefits associated with oral L-citrulline supplementation might be augmented by concomitant supplementation with exercise training in older adults. Abstract : Oral L-citrulline and exercise training influence vascular and muscular aging via improved nitric oxide bioavailability and muscle protein synthesis.